Is Moderate Intensity Cycling Sufficient to Induce Cardiorespiratory and Biomechanical Modifications of Subsequent Running?. Issue 4 (April 2017) - Walsh, Joel A.; Dawber, James P.; Lepers, Romuald; Brown, Marc; Stapley, Paul J.
Abstract : Abstract: Walsh, JA, Dawber, JP, Lepers, R, Brown, M, and Stapley, PJ. Is moderate intensity cycling sufficient to induce cardiorespiratory and biomechanical modifications of subsequent running? J Strength Cond Res 31(4): 1078–1086, 2017—This study sought to determine whether prior moderate intensity cycling is sufficient to influence the cardiorespiratory and biomechanical responses during subsequent running. Cardiorespiratory and biomechanical variables measured after moderate intensity cycling were compared with control running at the same intensity. Eight highly trained, competitive triathletes completed 2 separate exercise tests; (a) a 10-minute control run (no prior cycling) and, (b) a 30-minute transition run (TR) (preceded by 20-minute of variable cadence cycling, i.e., run versus cycle-run). Respiratory, breathing frequency ( f b ), heart rate (HR), cost of running (Cr ), rate constant, stride length, and stride frequency variables were recorded, normalized, and quantified at the mean response time (MRT), third minute, 10th minute (steady state), and overall for the control run (CR) and TR. Cost of running increased ( p ⩽ 0.05) at all respective times during the TR. The V[Combining Dot Above]E /V[Combining Dot Above]CO2 and respiratory exchange ratio (RER) were significantly ( p < 0.01) elevated at the MRT and 10th minute of the TR. Furthermore, overall mean increases were recorded for Cr, V[Combining Dot Above]E, V[Combining Dot Above]E /V[Combining Dot Above]CO2, RER, f b ( p < 0.01), and HR ( p ⩽ 0.05) during the TR. Rate constant values for oxygen uptake were significantly different between CR and TR (0.48 ± 0.04 vs. 0.89 ± 0.15; p < 0.01). Stride length decreased across all recorded points during the TR ( p ⩽ 0.05) and stride frequency increased at the MRT and 3 minutes ( p < 0.01). The findings suggest that at moderate intensity, prior cycling influences the cardiorespiratory response during subsequent running. Furthermore, prior cycling seems to have a sustained effect on the Cr during subsequent running.